Effects of Receiving Two Initial Feedings of Colostrum on the Average Daily Gain and Health of Pre-Weaning Group Housed Holstein Heifer Calves - Qiu-Di Zheng (MDPI AG, 2021)
We studied the effect on average daily gain (ADG) and health of an additional colostrum feeding to Holstein dairy heifers 12–16 h after the first colostrum feeding, provided within 2 h of birth. Calves (n = 190) with an average birth weight of 38.8 kg (29.5–52.6 kg) were randomly enrolled in blocks to either the control (CON) or colostrum (COL). The CON received 3 L of acidified pasteurized whole milk, and the COL received 3 L of pasteurized colostrum [average: 25.5 (24.7–26.4)% Brix]. Calves were group-housed, weighed, withers height measured weekly. Serum was obtained and analyzed with a% Brix refractometer. Mixed linear models were used to assess the differences in ADG, body weight, and height between the treatment and control. There was no difference in ADG between the COL and CON. However, serum % Brix was higher in the COL group (9.7%) than in the CON group (9.2%). Calves in the COL had more antibiotic treatments for respiratory diseases but fewer antibiotic treatments for otitis than the CON. In conclusion, providing an extra feeding of colostrum did not contribute to ADG of Holstein heifers during the pre-weaning period but did provide them with a higher total serum protein concentration.